Iron Scavenging in Aspergillus Species: Structural and Biochemical Insights into Fungal Siderophore Esterases. Issue 44 (27th August 2018) - Ecker, Felix; Haas, Hubertus; Groll, Michael; Huber, Eva M.
Abstract: Fungi utilize high‐affinity chelators termed siderophores with chemically diverse structures to scavenge the essential nutrient iron from their surroundings. Since they are among the strongest known Fe 3+ binding agents, intracellular release of the heavy metal atom is facilitated by the activity of specific hydrolases. In this work, we report the characterization and X‐ray crystal structures of four siderophore esterases: AfEstB and AfSidJ from Aspergillus fumigatus, as well as AnEstB and AnEstA from Aspergillus nidulans. Even though they all display the conserved α/β‐hydrolase fold, we found significant structural and enzymatic discrepancies in their adaption to both related and chemically diverse substrates. A structure of AfEstB in complex with its substrate triacetylfusarinine C gives insight into the active enzyme and shows tetrahedral coordination between the catalytic serine and the scissile ester bond. Abstract : Breaking the cage : Fungi use siderophores to scavenge Fe 3+ from the environment. Intracellular iron release occurs through hydrolysis of the siderophore backbone by esterases. Structural and biochemical analyses of two homologous EstB esterases, as well as EstA and SidJ, reveal how a common fold adapts to diverse substrates. A structure of an active enzyme in complex with its siderophore substrate reveals a tetrahedral intermediate at the catalytic serine.